2015
DOI: 10.1016/j.physa.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Looping dynamics of a flexible chain with internal friction at different degrees of compactness

Abstract: Recently single molecule experiments have shown the importance of internal friction in biopolymer dynamics. Such studies also suggested that the internal friction although independent of solvent viscosity has strong dependence on denaturant concentration. Recent simulations also support such propositions by pointing out weak interactions to be the origin of internal friction in proteins. Here we made an attempt to investigate how a single polymer chain with internal friction undergoes reconfiguration and loopi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…As expected with ν = 1/2 which corresponds to θ solvent, SDCRIF gives back "compacted Rouse with internal friction (CRIF)" [31], when k c and ξ int both are nonzero. A more realistic situation would be ν = 3/5 corresponding to good solvent.…”
Section: Solvent Quality Dependent Compacted Rouse With Internal supporting
confidence: 61%
See 3 more Smart Citations
“…As expected with ν = 1/2 which corresponds to θ solvent, SDCRIF gives back "compacted Rouse with internal friction (CRIF)" [31], when k c and ξ int both are nonzero. A more realistic situation would be ν = 3/5 corresponding to good solvent.…”
Section: Solvent Quality Dependent Compacted Rouse With Internal supporting
confidence: 61%
“…As the k c controls the compactness of the polymer, increasing the value of k c should result in the higher degree of internal friction. Since there is no first principle relation between k c and ξ int , we have used an ansatz in our calculation [12,31].…”
Section: A Equilibrium End To End Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] The inclusion of a resistive force proportional to the rate of change of the connector vector between beads in addition to the spring force has been shown to lead to a finite limiting value for the infinite frequency limit of the dynamic viscosity, 3 instantaneous stress jumps at the inception of steady shear flow, 5 and to a shear-rate dependent viscosity. 6,7 More recently, several experimental, [8][9][10][11][12] theoretical [13][14][15][16][17][18][19] and simulation studies [20][21][22][23] have shown that the presence of internal friction modulates conformational changes in a number of different biological contexts. This includes slowing down the process of protein folding, 8 affecting the dynamics of intermolecular interactions in intrinsically disordered proteins, 10,11 and influencing stretching transitions in single biomolecule force spectroscopy.…”
Section: Introductionmentioning
confidence: 99%